2003
DOI: 10.1046/j.1464-410x.2003.04364.x
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral resection of the prostate as catheter‐free day‐care surgery

Abstract: OBJECTIVE To evaluate the feasibility of transurethral resection of the prostate (TURP) as catheter‐free day‐care surgery. PATIENTS AND METHODS The study comprised 64 patients (mean age 62.4 years) with a mean (range) American Urological Association symptom score of 21.4 (9–31) and prostate volume (by ultrasonography) of 32.8 (17–50) mL, and with no significant comorbidity. The patients were admitted on the morning of the surgery and, under brief spinal anaesthesia, underwent standard TURP. After surgery the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
2
4

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 15 publications
7
34
2
4
Order By: Relevance
“…The duration of postoperative hospitalization and indwelling urethral catheterization has been signifi cantly reduced during the last decade [3][4][5] . Studies reported that early catheter removal has reduced the length of hospital stay, which in turn would be benefi cial to health care costs [1,6] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of postoperative hospitalization and indwelling urethral catheterization has been signifi cantly reduced during the last decade [3][4][5] . Studies reported that early catheter removal has reduced the length of hospital stay, which in turn would be benefi cial to health care costs [1,6] .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several practices of early catheter removal are used. Catheter removal on postoperative day 2, on postoperative day 1 and day-case prostatectomy can be accomplished in select patients if certain requirements can be satisfi ed [3][4][5] . From this study, the outcome, feasibility and safety of 431 consecutive patients for early catheter removal after TURP were examined.…”
Section: Introductionmentioning
confidence: 99%
“…Mebust et al [15] showed a mean duration of catheterization of 72 h after TURP. Recent studies [16,17] have suggested that the Foley catheter can be removed after TURP within 1 day in relatively young patients with moderate BPH and without chronic pulmonary or vascular disease. The mean age of patients in our study (72.33 years in the catheter-assisted and 71.13 years in the traditional TURP group) was higher than in previous studies (68.7 years in Gordon [16] and 62.5 years in Chander et al [17] ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies [16,17] have suggested that the Foley catheter can be removed after TURP within 1 day in relatively young patients with moderate BPH and without chronic pulmonary or vascular disease. The mean age of patients in our study (72.33 years in the catheter-assisted and 71.13 years in the traditional TURP group) was higher than in previous studies (68.7 years in Gordon [16] and 62.5 years in Chander et al [17] ). The mean volume of prostate resection in our study (26.2 ml in catheter-assisted and 24.68 ml in traditional TURP) was higher than in the studies by Gordon [16] (12.58 ml) and Chander et al [17] (22.1 ml).…”
Section: Discussionmentioning
confidence: 99%
“…Urologists unwilling to ignore patient expectations are pushed to find ways to shorten catheterization time following an operation. These efforts have led some to argue that a few hours of catheterization is sufficient while others argue that a suprapubic catheter be used instead of a foley catheter (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%